Detection of Toxoplasma gondii infection in feral wild boars (Sus scrofa) through indirect hemagglutination and PCR - Brandão,Laila Natasha Santos (2019)
ABSTRACT: Wild boars (Sus scrofa) have become an important invasive species in all Brazilian regions. Increase in their population causes damage to rural properties, as they invade and destroy crops. To protect their crops and farm animals, producers hunt wild boars and often consume the product without any sanitary control, becoming exposed to various types of pathogens, including Toxoplasma gondii. Sanitary evaluations of these animals are scarce, especially in relation to the protozoan T. gondii. This study aimed to evaluate the occurrence of this pathogen in wild boars in Brazil. We analyzed 122 blood samples from wild boars (blood clots and serum), collected between 2014 and 2016 in five Brazilian states, using polymerase chain reaction (PCR) and indirect hemagglutination (IH) techniques. In total, 33 (27%) samples were positive by at least one test, 16 (13.1%) were positive by PCR, 19 (15.6%) were positive by IH, and only 2 (1.6%) were positive by both tests. The lack of sanitary management of feral animals increases the incidence of infections, and the consumption of raw or inadequately cooked meat may become a potential source of infection for humans in Brazil.